2023
DOI: 10.5897/ajpp2023.5353
|View full text |Cite
|
Sign up to set email alerts
|

A review of phylogeny, medicinal values, phytochemistry and toxicity of Sarcophyte piriei Hutch (Balanophoraceae)

Abstract: In recent years, plants have shown potential as sources of antimicrobial agents due to their immense phytochemical constituents, and there is a need to continuously search and develop potent antimicrobial agents to combat the growing threat of antimicrobial resistance worldwide. The challenges facing the utilization of ethnomedicine are lack of sufficient studies to ascertain their therapeutic use. Sarcophyte is a holoparasite plant and trophic guild parasite. Its native ranges from Southern parts of Ethiopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Recently, Mbakazi et al (Mbakazi et al, 2022), Mohammed et al (Mahammed et al, 2020), and Dennis et al (Dennis et al, 2023) reported that the methanol stem extract of S. piriei possessed notable in vitro antibacterial activities against Enterococcus avium (MIC: 0.16 mg/mL; MBC: 1.25 mg/mL), Staphylococcus aureus, Klebsiella pneumonia, and Vibrio fluvialis (MIC: 0.625 mg/mL; MBC: 2.5 mg/ mL) based on disk diffusion and serial broth dilution methods. Also, using the same methods, they reported low activity of the methanol stem extract of S. piriei, which was not active against Escherichia coli (MIC: 0.625 mg/mL; MBC: >5 mg/mL) in comparison with the standard drug (streptomycin), whose average MIC was 2.2 × 10 −4 mg/mL (Mahammed et al, 2020;Mbakazi et al, 2022).…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mbakazi et al (Mbakazi et al, 2022), Mohammed et al (Mahammed et al, 2020), and Dennis et al (Dennis et al, 2023) reported that the methanol stem extract of S. piriei possessed notable in vitro antibacterial activities against Enterococcus avium (MIC: 0.16 mg/mL; MBC: 1.25 mg/mL), Staphylococcus aureus, Klebsiella pneumonia, and Vibrio fluvialis (MIC: 0.625 mg/mL; MBC: 2.5 mg/ mL) based on disk diffusion and serial broth dilution methods. Also, using the same methods, they reported low activity of the methanol stem extract of S. piriei, which was not active against Escherichia coli (MIC: 0.625 mg/mL; MBC: >5 mg/mL) in comparison with the standard drug (streptomycin), whose average MIC was 2.2 × 10 −4 mg/mL (Mahammed et al, 2020;Mbakazi et al, 2022).…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…The Sarcophyte genus belongs to the plant family Balanophoraceae and the order Santalales (sandalwood), according to the Angiosperm Phylogeny Group IV classification system ( Angiosperm Phylogeny Group, 2016 ; Nickrent, 2020 ). The family comprises 18 genera with over 100 species of root holoparasitic geophytes with a pantropical distribution ( Dennis et al, 2023 ). The genus Sarcophyte comprises a single species of two plants: Sarcophyte sanguinea Sparrm.)…”
Section: Introductionmentioning
confidence: 99%